2013
DOI: 10.2460/javma.243.11.1609
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of calf weaning weight and associated economic variables between beef cows with and without serum antibodies against or isolation from feces of Mycobacterium avium subsp paratuberculosis

Abstract: Calves from cows with MAP-positive test results had significantly lower AWWs than did calves from cows with MAP-negative test results, which translated into economic losses for MAP-infected beef herds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…Moreover, calves from cows that test positive for MAP and produce less milk are more likely to weigh less than calves from MAPnegative cows. A study conducted by Bhattarai et al (2013) supports this hypothesis. Those authors found that the 205-d adjusted weaning weight of suckler calves from cows with strongly positive ELISA results was 21.48 kg (47.26 lb) less than that of calves from cows testing MAP negative.…”
Section: Economic Impact Related To Weight Loss and Meat Productionsupporting
confidence: 77%
See 2 more Smart Citations
“…Moreover, calves from cows that test positive for MAP and produce less milk are more likely to weigh less than calves from MAPnegative cows. A study conducted by Bhattarai et al (2013) supports this hypothesis. Those authors found that the 205-d adjusted weaning weight of suckler calves from cows with strongly positive ELISA results was 21.48 kg (47.26 lb) less than that of calves from cows testing MAP negative.…”
Section: Economic Impact Related To Weight Loss and Meat Productionsupporting
confidence: 77%
“…The associated economic losses were estimated as $156.60/calf and $109.23/ calf for cows classified as heavy and moderate MAP shedders, respectively, and $57.49/calf for cows with strongly positive ELISA results. The results from the study conducted by Bhattarai et al (2013) indicate that the economic losses of paratuberculosis related to weight loss of calves in cattle production systems can be considerable. Similarly, the effect of MAP infections on slaughter weight and slaughter value of cows can be significant in terms of economic losses and animal welfare.…”
Section: Economic Impact Related To Weight Loss and Meat Productionmentioning
confidence: 95%
See 1 more Smart Citation
“…More than half of the responses from both producers and veterinarians favored culling calves based on a positive test or suspect clinical signs in the dam. While calves from test positive dams are reported to have lower weaning weights [31], one producer indicated that such calves can still be fattened and sent to slaughter, which would be economically more rewarding than immediate removal.…”
Section: Discussionmentioning
confidence: 99%
“…Raizman, Fetrow, and Wells () estimated the income over feed cost losses at $366 per MAP‐shedding cow per lactation, whereas Bhattarai et al. () estimated a loss of $1,644 US per 100 cows in a herd with a true prevalence of 7%. The cost of the disease to the US cattle industry was estimated at $250M US per year (Ott, Wells, & Wagner, ).…”
Section: Introductionmentioning
confidence: 99%